(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The article provides feedback on the specifics of social work with families. A family is a small group based on marriage or birth. The family is the basic unit of society, based on the couple. The role and place of the social worker in the process of social work with families is emphasized. The social worker seeks to create an environment in which the family can feel the environment as well as the family itself.